2017
DOI: 10.5219/850
|View full text |Cite
|
Sign up to set email alerts
|

Detection of selected heavy metals and micronutrients in edible insect and their dependency on the feed using XRF spectrometry

Abstract: Edible insect can be a valuable source of nutrients, but also a potential source of heavy metals. Quick detection of overlimit heavy metals concentration could be a key to processing and quick distribution of edible insect products. The aim of this work was to evaluate the feed-dependent content of heavy metals in the mealworm and superworm using the X-ray fluorescence spectrometry as an easy, cheap and a timeless screening method for evaluating the content of heavy metals and microelements. Using a handheld a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…For instance, feed ingredients such as wheat, rice, mussels, and animal kidney corns were shown to contain a high level of cadmium [102]. Mlček et al [103] reported that the accumulated heavy metal content is dependent on the feed and that the level of Pb in T. molitor larvae was below the detection limit, but the content of Cd in the dry matter of T. molitor larvae (147 to 230 mg/kg) was above the food limit. The accumulation of heavy metals in insects may be toxic to animals and humans.…”
Section: Safetymentioning
confidence: 99%
“…For instance, feed ingredients such as wheat, rice, mussels, and animal kidney corns were shown to contain a high level of cadmium [102]. Mlček et al [103] reported that the accumulated heavy metal content is dependent on the feed and that the level of Pb in T. molitor larvae was below the detection limit, but the content of Cd in the dry matter of T. molitor larvae (147 to 230 mg/kg) was above the food limit. The accumulation of heavy metals in insects may be toxic to animals and humans.…”
Section: Safetymentioning
confidence: 99%
“…In addition, it is necessary to verify the functional effects of insect products (e.g., chitin, bioactive compounds; [ 15 , 49 ]) that can be expected when used in swine diets. Furthermore, there are potential safety issues of insect products for toxic substances [ 50 ], antibiotic resistance gene [ 51 ], contamination by pathogens or mycotoxins [ 52 , 53 ], and heavy metal accumulation [ 54 ].…”
Section: Challenges In the Use Of Insect As A Feed Ingredientmentioning
confidence: 99%
“…The levels of selected elements in insects are dependent on food source, species and breeding environment. For example, the content of Cu and Zn in T. molitor was higher when fed with wheat bran than oat bran [13,28]. After eating feed containing Ni, Zn and Pb, the increased heavy metal content in the Spodoptera litura midgut, fat body, epidermis and hemolymph correlated with rising heavy metal concentrations in feed.…”
Section: Nonessential Mineral Elements In Edible Insectsmentioning
confidence: 98%
“…Edible insects are rich in nutritional value and are a potential source of minerals such as Cu, Fe, Mg, Mn, P, Se and Zn [28][29]. The extent of mineral accumulation varies with the element, the species, and the growth phase of the insect [21]; consequently, it is critical to understand the accumulation of essential minerals in edible insects to better utilize them in large-scale industrial production.…”
Section: Essential Mineral Elements In Edible Insectsmentioning
confidence: 99%